Comparative efficacy and acceptability of pharmacotherapies for postpartum depression: A systematic review and network meta-analysis - Zhang, Qing; Dai, Xiaoli; Li, Wei (Frontiers in Pharmacology, 2022)
Purpose: To evaluate the efficacy and tolerability of pharmacotherapies for postpartum depression (PPD). Method: We performed a computerized search of MEDLINE (Ovid and PubMed), EMBASE, Cochrane Library, Web of Science, and Google Scholar to identify eligible randomized controlled trials (RCTs) before March 31, 2022. We calculated standardized mean differences (SMD) for continuous outcomes and odd ratios (ORs) for dichotomous outcomes with the random-effects model. The tolerability of antidepressants in terms of early dropout was investigated. The surface under the cumulative ranking curve (SUCRA) was used for ranking the outcomes. Quality assessment of the included studies was performed with the Cochrane Collaboration’s tool. Results: A total of 11 studies with 944 participants were included in this network meta-analysis, involving nine antidepressants. With respect to efficacy, only oestradiol and brexanolone were significantly more effective relative to placebo (P<0.05), the calculated SUCRA indicated that oestradiol (94.3%) had the highest probability ranked first for reducing the PPD, and following were paroxetine (64.3%) and zuranolone (58.8%). Regarding tolerability, a greater percentage of patients treated with brexanolone experienced early dropout as compared to most other antidepressants. Conclusions: Only oestradiol and brexanolone showed significantly higher efficacy than placebo. According to the SUCRA ranking, oestradiol, paroxetine, and zuranolone were the three best antidepressants. Concerning acceptability in terms of early dropout, brexanolone is less well tolerated than other antidepressants.